Urban renewal after the Berlin Wall - Felix Richter; Gabriel Ahlfeldt; Wolfgang Maennig (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2013)
Urban renewal areas are popular instruments in spatial planning to prevent urban decline and to induce urban renewal. 22 renewal areas were implemented in Berlin, Germany alone between 1993 and 1995, mainly to increase housing and living quality in the aftermath of the city s long division during the Cold War period. We use a quasi-experimental research design to study the long-run effects of these designations on property prices within and surrounding the renewal areas. While there is evidence for significant improvements in the quality of the housing stock and increases in property prices in the targeted areas, evidence is weak at best for positive housing externalities. Our results further indicate that fundamental location advantages increase the impact of the policy.
Keywords: R12; R31; R58; 330